Genetic and non-genetic factors affecting first parity growth, reproductive and lactation traits in Barbari goats under semi-intensive management in semi-arid region of India - SINGH, M K; SINGH, S K; DIGE, M S; KUMAR, AKHILESH (The Indian Journal of Animal Sciences, 2021)
Barbari is most preferred goat breed of commercial farmers in India and information on its first parity growth, reproduction and production traits are valuable for making present and future genetic progress of flock. Data for present study pertains to 2,554 kids, progeny of 227 sires and 1645 dam born during 2001 to 2019 at Central Institute for Research on Goats, Makhdoom, Mathura, Uttar Pradesh. The least squares means of body weight of kids at birth, 3, 6, 9 and 12 months of age were 1.69±0.02, 7.48±0.13, 11.45±0.21, 16.08±0.28 and 20.21±0.33 kg, respectively. Period, sex, type of birth, and weight of dam at kidding were significant sources of non-genetic variation affecting body weights. The least squares mean of weight at first conception, weight at first kidding, age at first conception, age at first kidding and first gestation period were 18.04±0.07 kg, 21.79±0.09 kg, 381.65±2.51 days, 523.23±2.52 days and 143.33±0.21 days, respectively. Period of birth was major source of variation though these traits were also significantly affected by season and type of birth. The least squares means of first lactation 90-days milk yield, 140-days milk yield, total Lactation period milk yield, first lactation Length, milk yield per day of first lactation length and milk yield per day of first kidding interval were 50.22±0.41 litre, 69.94±1.05 litre, 57.32±0.53 litre, 123.01±0.53 days, 48.91±0.35 litre and 19.39±0.22 litres, respectively. Period, season, type of kidding, age and weight of dam at kidding were significant sources of non-genetic variation affecting above lactation traits. The h2 for growth and production traits were moderate whereas low to moderate for reproductive traits except weight at first conception and kidding which have moderate h2 estimates. The genetic and phenotypic correlations among the growth traits at different ages were moderate to high (0.3 to 0.8), however decrease with distant ages. Very high genetic and phenotypic correlation estimates were obtained among lactation traits suggesting that judicious selection of animals' for any lactation traits would yield consistent genetic improvement in the other milk production traits in the flock. The economic traits which were significantly influenced by non-genetic factors with high magnitude need attention for strategic management interventions such as planned breeding of females to avoid kidding in adverse weather conditions, better attention in suckling of milk for kids born with low birth weight, hygiene of shed, adequate supplementation of concentrate ration to those kids which have less pre-weaning growth regardless of type of birth, better nutrition level to maiden goats before and after mating and extension of weaning age for triplets by 10-15 days to obtain higher post weaning weight gains, optimization of breeding weight at first mating and strategic supplementary concentrate feeding as per milk yield.